2019
DOI: 10.1111/vco.12525
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated KIT as a predictor of outcome in canine mast cell tumours treated with toceranib phosphate or vinblastine

Abstract: Canine cutaneous mast cell tumour (MCT) is the most common malignant skin tumour in dogs and can exhibit variable biologic behaviour. Dysregulated signalling through the receptor tyrosine kinase (RTK) KIT can promote cell proliferation and survival, and assessment of its dysregulation via detection of activating c-kit gene mutations or assessment of KIT protein localization is associated with multiple features of malignancy. The aim of the current study was to use a previously validated immunohistochemical (IH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 24 publications
(54 reference statements)
0
21
0
Order By: Relevance
“…In the EU, the European Medicines Agency (EMA) has approved toceranib, tigilanol tiglate and mastinib mesylate (Masivet R ) (237). Of these approved or conditionally approved drugs, only toceranib (a multi-kinase inhibitor that inhibits c-kit, PDGFR, and VEGFR2), and mastinib (a c-kit inhibitor) can be used as a targeted drugs linked to specific genomic features of a tumor, as improvements in tumor response (43, 238) and outcome (239) have been demonstrated for tumors with an activating kit mutation; however, many targeted drugs used to treat human disease are currently used off-label in dogs (236,240). Many compounds developed (and FDA-approved) for use in humans underwent preclinical safety testing in dogs; significant safety and dosing data are thus available to help inform the treatment of canine cancer patients with these agents (241).…”
Section: Targeted Treatment Selectionmentioning
confidence: 99%
“…In the EU, the European Medicines Agency (EMA) has approved toceranib, tigilanol tiglate and mastinib mesylate (Masivet R ) (237). Of these approved or conditionally approved drugs, only toceranib (a multi-kinase inhibitor that inhibits c-kit, PDGFR, and VEGFR2), and mastinib (a c-kit inhibitor) can be used as a targeted drugs linked to specific genomic features of a tumor, as improvements in tumor response (43, 238) and outcome (239) have been demonstrated for tumors with an activating kit mutation; however, many targeted drugs used to treat human disease are currently used off-label in dogs (236,240). Many compounds developed (and FDA-approved) for use in humans underwent preclinical safety testing in dogs; significant safety and dosing data are thus available to help inform the treatment of canine cancer patients with these agents (241).…”
Section: Targeted Treatment Selectionmentioning
confidence: 99%
“…Even without observing the animals after tumor excision, the results obtained in the Grade 1 group suggest that canine MCT should not be considered benign in any histological grade, due to its variable biological behavior and prognosis. The biological behavior of canine MCTs [ 43 ] ranges from solitary benign nodules to systemic metastatic tumors, which hinders the accuracy of prognosis and choice of treatment [ 17 ]. In addition, our study did not evaluate the presence of metastases, which would be relevant, as dogs with distant metastases had significantly shorter survival than those with regional lymph node metastases [ 44 ], which are also a negative prognostic indicator, regardless of histological grade [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although exon 11 mutations are the most common mutations in cutaneous MCTs, mutations at other sites were not assessed in this study and should be considered in future studies. Additionally, recent studies have shown that measuring the KIT phosphorylation status by IHC is an additional tool to determine the c ‐KIT activation status 41,42 . Further research is needed to determine the relationship between c ‐KIT mRNA expression and KIT phosphorylation.…”
Section: Discussionmentioning
confidence: 99%